Selective precipitation of schwertmannite in a stratified acidic pit lake of Iberian Pyrite Belt. (2nd January 2018) - Santofimia, E.; López-Pamo, E.; Montero, E.
Abstract: Selective precipitation of schwertmannite was identified in the water column of a chemically stratified acidic lake (pH 2.0 2.5). A set of analytical techniques was used to identify accurately the mineral phase (X-ray diffraction, X-ray fluorescence spectrometry, scanning electron microscopy coupled with energy dispersive spectroscopy). The lake has two clearly differentiated layers: a thin superficial layer that extends to ∼2 m in depth with less dissolved solid content and, therefore, lower density, which contrasts with a thicker lower layer that extends to 34 m in depth. The upper layer is strongly influenced by climatic factors, triggering dilution (rainfall), concentration (dry season) and intense seasonal thermal fluctuations, while the lower layer is more compositionally and thermally stable. Schwertmannite precipitate was initially observed only in the upper layer, adhered to a plastic buoy and the anchor line. The latter was confirmed through a test involving a precipitation device that consisted of maintaining a series of plastic plates at different depths over a period of several months. Only the plates located in the upper layer became covered with precipitate, whereas the plates that were submerged in the lower layer remained clean. These observations clearly differed from the saturation indices of schwertmannite (SIsch ) calculated using PHREEQC and using Bigham et al. (1996) or Kawano and Tomita (2001) solubility products. Schwertmannite would not precipitate in the lake with the former but would precipitate in both layers with the latter. It is the constant provided by Yu et al. (1999) that makes SIsch in both layers approach the observed behaviour: SIsch >0 displays oversaturation in the upper layer while SIsch <0 displays undersaturation in the lower layer. The value of the product of solubility that better adjusts to this situation is log Ksch = 9.5 10. Using the method by Yu et al. (1999) to establish the apparent solubility, a range of log Ksch values was defined between 10.5 and 11.5 for the system studied.